1996
DOI: 10.1046/j.1365-3156.1996.d01-85.x
|View full text |Cite
|
Sign up to set email alerts
|

Mefloquine tolerability during chemoprophylaxis: focus on adverse event assessments, stereochemistry and compliance

Abstract: SummaryThis longitudinal study of travellers to Africa taking mefloquine ( M Q ) chemoprophylaxis aimed to quantify and assess non-serious adverse events (AE) occurring during short-term prophylaxis and relate these to concentrations of racemic MQ, its enantiomers and metabolite. A total of 420 volunteers ( 5 2 % F) participated. AEs with some impact on activities were reported by I I .2% of participants including 7.9 % of neurological/psychiatric symptoms. Women were more likely to report AEs (P=0.02). The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
43
1
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 17 publications
1
43
1
1
Order By: Relevance
“…These findings suggested that plasma tafenoquine concentrations are not the primary predictor of tafenoquine tolerability. This lack of an association between plasma drug concentrations and adverse events has also been seen with another antimalarial agent, mefloquine, which shares similar pharmacokinetic properties with tafenoquine (12) in that both are lipophilic, are slowly absorbed from the gastrointestinal tract, are extensively bound to tissues, and have elimination t 1/2 values of about 2 weeks (1, 2, 9, 14).…”
Section: Discussionmentioning
confidence: 81%
“…These findings suggested that plasma tafenoquine concentrations are not the primary predictor of tafenoquine tolerability. This lack of an association between plasma drug concentrations and adverse events has also been seen with another antimalarial agent, mefloquine, which shares similar pharmacokinetic properties with tafenoquine (12) in that both are lipophilic, are slowly absorbed from the gastrointestinal tract, are extensively bound to tissues, and have elimination t 1/2 values of about 2 weeks (1, 2, 9, 14).…”
Section: Discussionmentioning
confidence: 81%
“…A modified version of this screen was used here. Female rats were selected since the neurological effects of mefloquine in humans are more often observed in women (18,19,36). This may be due to higher plasma concentrations or areas under the curve (19), but a gender bias cannot be ruled out.…”
mentioning
confidence: 99%
“…This may be due to higher plasma concentrations or areas under the curve (19), but a gender bias cannot be ruled out. We chose a 72-h observation window because neurological effects in humans are most often observed during this time frame (18,36). Finally, in an attempt to put any neurological findings observed into a clinical context, plasma mefloquine concentrations were determined in order to guide dose selection.…”
mentioning
confidence: 99%
“…Some studies have shown that more women than men report neurological or psychiatric adverse events (WHO 1991;Phillips-Howard & ter Kuile 1995;ter Kuile et al 1995;Schlagenhauf et al 1996). Therefore, gender should also be taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Weinke et al (1991) estimated the incidence of neuropsychiatric adverse reactions during prophylaxis as 1:1300; by comparison a recent retrospective study found that disabling neuropsychiatric side-effects occurred in 1:140 of travellers taking mefloquine for prophylaxis (Barrett et al 1996). Another recent study showed that 7.9% (33:420) of travellers taking mefloquine reported minor neuropsychiatric adverse effects, but no serious adverse effects (Schlagenhauf et al 1996). In 1996 the Department of Drug Safety of F. Hoffmann-La Roche reported a total of 3827 adverse events, 87 for curative treatment.…”
Section: Discussionmentioning
confidence: 99%